Peningkatan Hasil Belajar Peserta Didik dengan Metode Jiqsaw pada Materi Hierarki Gereja Katolik terhadap Fase F Kelas XI SMK Cinta Kasih Tzu Chi- Cengkareng - Eduardus Laot (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2025)
This study aims to determine the improvement of learning hierarchy in the Catholic church in class XI students through the Jigsaw learning model. The research was conducted at SMK Cinta Kasih Tzu Chi, Cengkareng, West Jakarta.The implementation of the research consisted of two cycles, each cycle consisting of four stages, namely planning, action implementation, observation, and reflection. Based on this research, it was concluded that by using the Jigsaw learning model the learning outcomes of understanding the hierarchy of the Catholic church could increase. The results of this study are useful for improving the quality of learning Catholic religious education in general and especially in understanding the Catholic church hierarchy effectively. The researcher's suggestion on this occasion is that Catholic religion teachers continue to strive to improve the quality of learning by using a variety of varied learning models.